High Levels of Heavy Metal(loid)s Related to Biliary Hyperplasia in Hedgehogs (Erinaceus europaeus) - Catarina Jota Baptista; Fernanda Seixas; José M. Gonzalo-Orden; Carla Patinha; Pedro Pato; Eduardo Ferreira da Silva; María Casero; Erica Brazio; Ricardo Brandão; Daniela Costa; Teresa Letra Mateus; Paula A. Oliveira (Animals, 2023)
Heavy metal(loid) pollution of ecosystems is a current One Health problem. The liver is one of the most affected organs in cases of acute or chronic exposure to abnormal amounts of these substances, inducing histopathologic lesions. In order to assess the influence of heavy metal(loids), forty-five European hedgehogs (Erinaceus europaeus) were submitted to necropsy, and liver samples were collected for a routine histopathology exam and metal(loid)s determination (As, Cd, Co, Cr, Cu and Pb) by ICP-MS. Age was estimated during the necropsy exam. Biliary hyperplasia was the most frequent lesion observed (16/45; 35.56%). No statistically significant associations were found between biliary hyperplasia and age or sex. Metal(loid)s’ concentrations were higher in animals with biliary hyperplasia (except for As). There was a statistically significant difference for both Cd and Co. For As, Cd and Co, cubs and juveniles animals showed significantly lower concentrations than elder individuals. Only for Pb were significant differences found between females and males. As described in the literature, exposure to metal(loid)s may be a cause of biliary hyperplasia, although further research (including the use of biochemical methods) is needed to support these results. To the authors’ knowledge, this is the first report of this association in hedgehogs.